Implementasi Manajemen Konflik dalam Menyelesaikan Persoalan Kedisiplinan Santri di Pondok Pesantren Al-Azhar Jember - Hayyah, Fanniatul; Nuri Firdausiyah; Risma Dwi Yuliana; Mua’limin Mua’limin (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
This research aims to examine in depth the application of conflict management in overcoming student discipline problems at the Al-Azhar Jember Islamic Boarding School. Conflict management acts as an effective preventive key to overcoming challenges in maintaining discipline. The research method used is descriptive qualitative, with data collection through interviews and observation. The research results show that conflict management is an effective step to overcome challenges in maintaining discipline, especially among PP students. Al-Azhar. There are several findings from the results of the research conducted: 1) Conflict management planning steps in resolving student discipline problems in PP. Al-Azhar Jember, 2) Parties Involved in Conflict Management Planning in Resolving PP Student Discipline Problems. Al-Azhar Jember, 3) Objectives of Conflict Management in PP. Al-Azhar Jember.